Tutelas jurisdicionais de urgência em reação ao dano ambiental no novo código de processo civil - Barbosa Junior, Vitor Berenguer (2016)
The life in society, in order to be harmonic and peaceful, needs clear, precise and accessible rules, and that materializes trough the law. The jus positum projects itself to not only establish parameters to the individuals living in the same space, but also align their relations with the environment. The relations transcend the merely human range to reach the environmental range. Nevertheless, the existence of rules don’t assure the effectiveness tutelage of those rights, there are needs of useful tools that ensures the effectiveness of those constituted norms, therefore, the procedural law acquire a prominent role of a legitimate instrument that ensures the tutelage of the violated or threatened right throughout him. Concerning the environmental law, that subject gets even more complex configuration, because, beyond the necessity of that instrument to ensure the jurisdictional tutelage, and that is the due process of law, there is a need of celerity end effectiveness over the process, itself. In this current year occurred that the New Civil Procedural Code had invigorated, crafted with the purpose to ensure better cohesive text e closer proximity with the norms and constitutional principles, such an instrument has in its core the urgency tutelage, and that, in our vision, is the main disposed procedural instrument regarding the environmental protection.